2007
DOI: 10.1097/jto.0b013e31811f472a
|View full text |Cite
|
Sign up to set email alerts
|

A Web Site on Lung Cancer: Who Are the Users and What Are They Looking For?

Abstract: Given the number of visitors to the lung cancer Web site, it can be concluded that there is a great need for additional information among patients and caregivers. The launched Web site www.longkanker.info has reached its goal of providing a dependable source of information about lung cancer and satisfying its visitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
4
18
0
1
Order By: Relevance
“…Thus, those at increased risk of developing type 2 diabetes mellitus were interested in learning more on the subject both through interactive features and through reading materials. Other studies on the use of Internet-based health information have shown that Internet users prefer the presentation of the information in an interactive format or as animation [24,56]. The fact that those who calculated higher scores remained on the website longer creates opportunities for more targeted information and suggestions for higher risk persons.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, those at increased risk of developing type 2 diabetes mellitus were interested in learning more on the subject both through interactive features and through reading materials. Other studies on the use of Internet-based health information have shown that Internet users prefer the presentation of the information in an interactive format or as animation [24,56]. The fact that those who calculated higher scores remained on the website longer creates opportunities for more targeted information and suggestions for higher risk persons.…”
Section: Discussionmentioning
confidence: 96%
“…However, to ensure that a high quality health website is used to its full potential, an evaluation of its use in a real-life setting seems paramount. While some research on the use of disease information pages exists [24,25], no studies have yet investigated the use of risk calculator websites in real-life setting. To facilitate future development of high-quality risk websites and enhance their public health impact, we analyze the use of a webbased tool to calculate the risk of developing type 2 diabetes mellitus in the next 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the launch and development of a Dutch cancer information source found that half of the visitors found the websites through search engines or links from other sites and that the number of accesses increased over time (10). The study also revealed that most visitors were able to find the information they wanted and that caregivers were the most popular visitors (57%).…”
Section: Use Of the Internet In Cancer Patients And Caregiversmentioning
confidence: 76%
“…The unique quality of the DLIC is that it was set up at the national level and broadly supported by both health care professionals and patient groups. Following its creation, a special section was added to its website—an interactive webpage, called “Ask the physician”, where visitors could anonymously ask an online lung specialist questions and receive an answer within 48 hours [6]. It was after some scepticism from the lung specialists involved in the website’s management and content that this new section was launched [6].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the most popular page of the website is the “Ask the Physician” page. Our study group has previously investigated who was visiting the interactive webpage and what the information visitors were looking for [6,8]. Seventy-four percent of the questions (n=1893) were not only asked by lung cancer patients (13%) but also in large numbers by their informal caregivers (61%, eg, family, friends, and loved ones).…”
Section: Introductionmentioning
confidence: 99%